SHE - revista portafolio Sara Henao (2024)
I'm Sara, Crossmedia Designer. A passionate Crossmedia Designer specialized in illustration, art direction, graphic design and marketing. My Crossmedia approach ensures an effective integration in diverse platforms, standing out in aesthetics, communication and emotional connection. Committed to boosting the identity and message of each project. She is my creative version, she is the one that shows up when it's my time to create and innovate.